2008
DOI: 10.1172/jci34450
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of FHL1 as the protein mutated in human reducing body myopathy

Abstract: Reducing body myopathy (RBM) is a rare disorder causing progressive muscular weakness characterized by aggresome-like inclusions in the myofibrils. Identification of genes responsible for RBM by traditional genetic approaches has been impossible due to the frequently sporadic occurrence in affected patients and small family sizes. As an alternative approach to gene identification, we used laser microdissection of intracytoplasmic inclusions identified in patient muscle biopsies, followed by nanoflow liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
168
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(188 citation statements)
references
References 38 publications
18
168
1
1
Order By: Relevance
“…Immunohistochemical analysis of RBM patients' muscle indicated that clinical severity might be correlated with the amount of residual FHL1 protein, and differential reduction in FHL1 amount was also observed in affected males and females from a SPM family with FHL1 mutation. 10,12 Unfortunately, the amount of FHL1 protein could not be assessed on muscle biopsies from our patients and further studies are warranted.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Immunohistochemical analysis of RBM patients' muscle indicated that clinical severity might be correlated with the amount of residual FHL1 protein, and differential reduction in FHL1 amount was also observed in affected males and females from a SPM family with FHL1 mutation. 10,12 Unfortunately, the amount of FHL1 protein could not be assessed on muscle biopsies from our patients and further studies are warranted.…”
Section: Discussionmentioning
confidence: 96%
“…[9][10][11][12][13][14][15][16][17]21 The available genotype-phenotype data indicate that patients belonging to the 'RB subgroup' harbour missense mutations or short in-frame deletions affecting the second LIM domain, whereas mutations found in XMPMA and EDMD/ EDMD-like patients are either missense, in-frame or out-of-frame mutations localized in the more distal exons encoding the third and fourth LIM domains. 17,21 Histidine 123 and cysteine 224 appear as the main mutation hot spots for RBM and XMPMA, mutated in 7/15 and 5/9 families, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por ello, la caída, descomposición y liberación de nutrientes de la hojarasca son procesos funcionales claves que pueden suministrar información esencial acerca del desarrollo fenológico, vitalidad y variación anual como reacción al clima y a otros cambios ambientales (Schessl et al, 2008). Las investigaciones en el trópico han comparado ecosistemas manejados y no intervenidos (Del Valle, 2003;Dale y Polasky, 2007) y han determinado la importancia de esta hojarasca en la creación de refugios para la conservación de la biodiversidad (Perfecto et al, 1996).…”
Section: Introductionunclassified